2009
DOI: 10.1007/s12562-009-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of density contrast and sound-speed contrast for target strength estimation of Neocalanus copepods (Neocalanus cristatus and Neocalanus plumchrus) in the North Pacific Ocean

Abstract: Abstract:The mass density and sound-speed contrasts against surrounding seawater (g and h, respectively) of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…The overall magnitudes of the measured density values for C. finmarchicus and the slightly increasing trend in g from fall to spring are also in agreement with previous studies on the same species conducted at the higher latitudes of the Northeast Atlantic (Køgeler et al 1987;Knutsen et al 2001). Other studies from the North Pacific on large Neocalanus copepods also found g values in a similar range (Matsukura et al 2009;Smith et al 2010). The low g values for calanoid copepods relative to other zooplankton, reaching close to neutral buoyancy before overwintering, are generally explained by the hypothesis that the lipid content and composition are part of a buoyancy regulation strategy (Visser and Jónasdóttir 1999;Campbell and Dower 2003;Pond 2012).…”
Section: Finmarchicussupporting
confidence: 90%
“…The overall magnitudes of the measured density values for C. finmarchicus and the slightly increasing trend in g from fall to spring are also in agreement with previous studies on the same species conducted at the higher latitudes of the Northeast Atlantic (Køgeler et al 1987;Knutsen et al 2001). Other studies from the North Pacific on large Neocalanus copepods also found g values in a similar range (Matsukura et al 2009;Smith et al 2010). The low g values for calanoid copepods relative to other zooplankton, reaching close to neutral buoyancy before overwintering, are generally explained by the hypothesis that the lipid content and composition are part of a buoyancy regulation strategy (Visser and Jónasdóttir 1999;Campbell and Dower 2003;Pond 2012).…”
Section: Finmarchicussupporting
confidence: 90%
“…For the measurement of copepod body mass density, McAllen et al (1998) used a solution of sea salts and deionized water. The density bottle method introducing adult copepods to different mixtures of seawater and glycerol was also used by Greenlaw (1977) and Matsukura et al (2009). Køgeler et al (1987) and Visser & Jonasdottir (1999) used the density gradient column method with solutions of diluted seawater and sugar.…”
Section: Effect Of Salinity On Adult Respiration Ratementioning
confidence: 99%
“…Their results showed that the maximum TS values for E. pacifica, calculated from a theoretical scattering model, changed by about 5 dB from spring to autumn. Furthermore, Matsukura et al [23] suggested that g and h are affected by seasonal changes in lipid profiles. In this study, the larval anchovy g and h values were fixed at 1.068 and 1.037, respectively.…”
Section: Discussionmentioning
confidence: 99%